1990
DOI: 10.1111/j.1365-2125.1990.tb03671.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nicardipine on the pharmacokinetics and pharmacodynamics of propranolol in healthy volunteers.

Abstract: 1 The influence of a single oral dose of nicardipine 30 mg on the pharmacokinetics and pharmacodynamics of propranolol 80 mg was investigated in twelve healthy volunteers. 2 Co-administration of nicardipine significantly increased the AUC and the mean Cmax of propranolol. 3 Blood pressure and heart rate tended to decrease more when propranolol and nicardipine were administered together than when propranolol was given alone, but differences are of doubtful significance. 4 The results indicate that nicardipine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Not only CYP3A4 and CYP2D6, but essentially all CYP forms investigated in the present study were also inhibited by nicardipine in vitro as reported by Katoh et al 19) This may account for a reported in vivo pharmacokinetic interaction between nicardipine and other drugs such as propranolol. 20,21) Considering the mechanism of inhibition, a competitive inhibition of these CYPs was suggested in the present study (data not shown). In conclusion, nicardipine can be metabolized mainly by human CYP2C8, CYP2D6 and CYP3A4, whereas it could be a relatively potent competitive inhibitor of these CYPs.…”
Section: Discussionmentioning
confidence: 62%
“…Not only CYP3A4 and CYP2D6, but essentially all CYP forms investigated in the present study were also inhibited by nicardipine in vitro as reported by Katoh et al 19) This may account for a reported in vivo pharmacokinetic interaction between nicardipine and other drugs such as propranolol. 20,21) Considering the mechanism of inhibition, a competitive inhibition of these CYPs was suggested in the present study (data not shown). In conclusion, nicardipine can be metabolized mainly by human CYP2C8, CYP2D6 and CYP3A4, whereas it could be a relatively potent competitive inhibitor of these CYPs.…”
Section: Discussionmentioning
confidence: 62%
“…However, an interaction has been reported between nicardipine and propranolol [31]. It was suggested that this interaction could be explained by a decrease in the hepatic clearance of propranolol by mechanisms such as decreased microsomal drug oxidation activity or functional shunting in the liver [31]. Such mechanisms also could explain our results.…”
Section: Interaction Of Nicardipine With Metoprololmentioning
confidence: 52%
“…Also, the plasma S-(-)-metoprolol concentration vs ,B-adrenoceptor blocking effect curve was similar whether or not nicardipine was combined with metoprolol. This was also the case in a study of the interaction between nicardipine and propranolol [31].…”
Section: Interaction Of Nicardipine With Metoprololmentioning
confidence: 60%
“…Combination therapy of a fl-adrenoreceptor blocker and a calcium antagonist is increasingly being used and has been reported to be more effective and to have an improved adverse effect profile compared to monotherapy with either drug for blood pressure lowering and antianginal effects [1][2][3].We recently demonstrated that, in healthy volunteers, a single oral dose of 30 mg nicardipine significantly increased the bioavailability of a single oral dose of 80 mg propranolol [4]. This increase in bioavailability could theoretically result from either an increased absorption from the gastrointestinal tract or a decreased hepatic "first-pass" clearance.…”
mentioning
confidence: 99%
“…An increased absorption is unlikely as more than 95% of a single oral dose of propranolol monotherapy is already absorbed from the gastrointestinal tract [5]. This could result from a metabolic inhibition at the level of cytochrome P450, as suggested by recent in vitro findings in rat hepatocytes [7], although it may also be related to a transient increase in splanchnic and hepatic blood flow, causing a functional shunt in the liver similar to the propranolol mechanism for the propranolol-food interaction [4,[8][9][10]. A more likely explanation is a decrease in hepatic clearance of propranolol when coadministered with nicardipine.…”
mentioning
confidence: 99%